The Influence of Technology Acceptance Model (TAM) on The Users’ Behavior of Sikesya Application in IAIN Surakarta - Tri Wahyuni (Shirkah: Journal of Economics and Business, 2016)
This study aims to evaluate the student acceptance of SIKESYA  (Sharia Financial System/Sikesya) application as the users by using the framework of Technology Acceptance Model (TAM) and its development. The constructs being tested in this research are perceived usefulness, perceived ease of use, experience, social influence, attitute toward behavior, behavioral intention, facilitating condition, and user behaviors. As much as 80 students has been chosen as sample which were determined using purposive sampling method. The data gathered was then analyzed using partial least square (PLS). The result showed that experience did not influence the perceived ease of use, on the other hand perceived usefulness has a positif influence toward users attitude and behavior in using Sikesya, while the perceived ease of use did not influence the users atttitude and  behavior at all, since the students would still use it as it is an application used as part of university services. The attitude and behavior did not influence the behavioral intention, whereas the social influence has a positif effect on behavioral intention, yet the behavioral intention gave positif impact to user’s behavior. On the other hand, facilitating condition has no effect toward users’ behavior. Keywords: Sharia Financial System (SIKESYA), Technology Acceptance Model (TAM), IAIN Surakarta